The plant energy-dissipating mitochondrial systems: Depicting the genomic structure and the expression profiles of the gene families of uncoupling protein and alternative oxidase in monocots and dicots - Borecký, Jiří; Nogueira, Fábio T. S.; De Oliveira, Kívia A. P.; Maia, Ivan de Godoy [UNESP]; Vercesi, Aníbal E.; Arruda, Paulo (Oxford University Press (OUP), 2006)
The simultaneous existence of alternative oxidases and uncoupling proteins in plants has raised the question as to why plants need two energy-dissipating systems with apparently similar physiological functions. A probably complete plant uncoupling protein gene family is described and the expression profiles of this family compared with the multigene family of alternative oxidases in Arabidopsis thaliana and sugarcane (Saccharum sp.) employed as dicot and monocot models, respectively. In total, six uncoupling protein genes, AtPUMP1-6, were recognized within the Arabidopsis genome and five (SsPUMP1-5) in a sugarcane EST database. The recombinant AtPUMP5 protein displayed similar biochemical properties as AtPUMP1. Sugarcane possessed four Arabidopsis AOx1-type orthologues (SsAOx1a-1d); no sugarcane orthologue corresponding to Arabidopsis AOx2-type genes was identified. Phylogenetic and expression analyses suggested that AtAOx1d does not belong to the AOx1-type family but forms a new (AOx3-type) family. Tissue-enriched expression profiling revealed that uncoupling protein genes were expressed more ubiquitously than the alternative oxidase genes. Distinct expression patterns among gene family members were observed between monocots and dicots and during chilling stress. These findings suggest that the members of each energy-dissipating system are subject to different cell or tissue/organ transcriptional regulation. As a result, plants may respond more flexibly to adverse biotic and abiotic conditions, in which oxidative stress is involved. © The Author [2006]. Published by Oxford University Press [on behalf of the Society for Experimental Biology]. All rights reserved.
Keywords: Alternative oxidase; Expression profile; Oxidative stress; Uncoupling proteins; Genes; Plants (botany); Proteins; Sugar cane; Tissue; Dicots; Monocots; Energy dissipation; alternative oxidase; carrier protein; ion channel; membrane protein; messenger RNA; mitochondrial protein; mitochondrial uncoupling protein; oxidoreductase; vegetable protein; amino acid sequence; Arabidopsis; biology; cold; comparative study; enzymology; gene expression profiling; genetics; genome; metabolism; mitochondrion; molecular genetics; multigene family; phylogeny; physiology; reverse transcription polymerase chain reaction; sequence alignment; sequence analysis; sugarcane; Amino Acid Sequence; Carrier Proteins; Cold; Computational Biology; Gene Expression Profiling; Genome, Plant; Ion Channels; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Molecular Sequence Data; Multigene Family; Oxidoreductases; Phylogeny; Plant Proteins; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Saccharum; Sequence Alignment; Sequence Analysis, Protein; Energy; Genotypes; Plant Tissues; Plants; Sugar Cane; Arabidopsis thaliana; Dicotyledoneae; Liliopsida; Saccharum hybrid cultivar; Saccharum sp.